An experimental energy consumption comparison between trajectories generated by using the cart-table model and an optimization approach for the Bioloid robot. (9th April 2020) - Tacué, Jeison; Rengifo, Carlos; Bravo, Diego
The aim of this article is to present a statistical comparison of the electric energy expenditure between two techniques for the generation of gait patterns in biped robots. The first one is to minimize the sum of the squared torques applied to the joints of the robot, and the second one is based on the cart-table model. For the experiments, we measured the energy delivered by the battery of the robot to the servomotors. We applied the two aforementioned methods for three velocities (0.5, 1.0, and 1.3 m/min). Additionally, each combination of method and velocity was performed by the robot 10 times. The energy expenditure for each method was compared by applying the Wilcoxon test. In all comparisons, the value of p was lower than 0.004, indicating that the differences were statistically significant. The optimization approach leads to a reduction in energy expenditure that ranged from 9.16 % to 13.35 %. The conclusion is that all the effort required to implement an approach that requires a complete dynamic model of the robot allows a significant reduction in energy consumption.